A three‐component signalling system fine‐tunes expression kinetics of HPPK responsible for folate synthesis by positive feedback loop during stress response of X anthomonas campestris - Fang‐Fang Wang; Chao‐Ying Deng; Zhen Cai; Ting Wang; Li Wang; Xiao‐Zheng Wang; Xiao‐Ying Chen; Rong‐Xiang Fang; Wei Qian (Environmental Microbiology, 2014)
Summary During adaptation to environments, bacteria employ two‐component signal transduction systems, which contain histidine kinases and response regulators, to sense and respond to exogenous and cellular stimuli in an accurate spatio‐temporal manner. Although the protein phosphorylation process between histidine kinase and response regulator has been well documented, the molecular mechanism fine‐tuning phosphorylation levels of response regulators is comparatively less studied. Here we combined genetic and biochemical approaches to reveal that a hybrid histidine kinase, SreS , is involved in the SreK ‐ SreR phosphotransfer process to control salt stress response in the bacterium X anthomonas campestris . The N ‐terminal receiver domain of SreS acts as a phosphate sink by competing with the response regulator SreR to accept the phosphoryl group from the latter's cognate histidine kinase SreK . This regulatory process is critical for bacterial survival because the dephosphorylated SreR protein participates in activating one of the tandem promoters ( P 2) at the 5′ end of the sreK ‐ sreR ‐ sreS ‐ hppK operon, and then modulates a transcriptional surge of the stress‐responsive gene hppK , which is required for folic acid synthesis. Therefore, our study dissects the biochemical process of a positive feedback loop in which a ‘three‐component’ signalling system fine‐tunes expression kinetics of downstream genes.